2008
DOI: 10.1103/physrevb.77.054108
|View full text |Cite
|
Sign up to set email alerts
|

Structure, phase transformations, and defects ofHfO2andZrO2nanoparticle

Abstract: Structure, phase transformations, grain growth, and defects of bare and alumina-coated nanoparticles of HfO 2 and ZrO 2 synthesized in a microwave-plasma process have been investigated by x-ray diffraction ͑XRD͒, transmission electron microscopy ͑TEM͒, and perturbed angular correlation ͑PAC͒ spectroscopy. The PAC technique was used to measure the electric quadrupole interactions ͑QIs͒ of the nuclear probes Ta in the bulk oxides was determined in the same temperature range 300 K ഛ T ഛ 1550 K. The oxygen-metal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 49 publications
5
18
0
5
Order By: Relevance
“…For these reasons, HfO 2 has been extensively studied by means of TDPAC. 3 The TDPAC technique provides a high-resolution determination of quadrupolar electric, dipolar magnetic hyperfine interactions, or a combination of both. 4 The electric quadrupolar interaction is essentially given by the product of the nuclear quadrupole moment, Q, characteristic of a given nuclear state of spin I, and the electric field gradient ͑EFG͒ at the nuclear site.…”
Section: Hf͑→ 181mentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons, HfO 2 has been extensively studied by means of TDPAC. 3 The TDPAC technique provides a high-resolution determination of quadrupolar electric, dipolar magnetic hyperfine interactions, or a combination of both. 4 The electric quadrupolar interaction is essentially given by the product of the nuclear quadrupole moment, Q, characteristic of a given nuclear state of spin I, and the electric field gradient ͑EFG͒ at the nuclear site.…”
Section: Hf͑→ 181mentioning
confidence: 99%
“…Ayala et al 9 reported a second interaction in coarse grained m-HfO 2 characterized by high V ZZ and values. Forker et al 3 investigated the structure, phase transformations, grain growth, and defects of coarse-grained and bare nanoparticles of m-HfO 2 synthesized in a microwave plasma. The authors found that, in addition to the well-known HFI1, a second component involving 20-30 % of the probe nuclei appeared in the 181 Ta PAC spectra.…”
Section: Hf͑→ 181mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, investigations of thin films [121,122] and nanoparticles [123] of HfO 2 have been reported. The last reference is particularly important for this chapter.…”
Section: Defects and Diffusion Studied Using Pac Spectroscopymentioning
confidence: 99%
“…The last reference is particularly important for this chapter. Indeed, the formation of probe-defect complexes (and insights into the nature of these defects) in hafnia nanoparticles was studied in great detail as a function of the thermal history of the samples by Forker et al [123] by means of PAC experiments using 181 Ta as probe. Before the results obtained by Forker et al using hafnia nanoparticles are discussed, it is important to describe the results, obtained by the same group, in commercial coarse-grained (cg) HfO 2 .…”
Section: Defects and Diffusion Studied Using Pac Spectroscopymentioning
confidence: 99%